2018
DOI: 10.15237/gida.gd17107
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Listeria Spp. In Raw Milk and Dairy Products Retailed in Ankara

Abstract: The objective of this study was to determine the prevalence of Listeria species in raw milk, and dairy products. A total of 110 samples were obtained from randomly selected retail stores and local bazaars located in Ankara. Using TS EN ISO 11290-1 method, 23 samples were found positive for Listeria spp. The overall prevalence of Listeria spp. was 20.91%, in which L. innocua was the most commonly recovered species (6.36%). The remaining isolates were identified as L ivanovii (5.45%), L. monocytogenes (4.55%), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
4
8
1
Order By: Relevance
“…Genes iap and hlyA are responsible for host cell invasion, while the actA gene is associated with cell-to-cell spread. Our finding agreed with those of previous studies conducted by Tahoun et al, and Şanlibaba et al [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], in which virulence genes were determined in L. monocytogenes isolated from raw milk, animals, and environmental samples. Our findings in virulence gene detection are also supported by the findings of [ 23 ], who reported that virulence genes hlyA , iap, and actA were the most recognized, with prevalence rates of 70.6%, 70.6%, and 52.9%, respectively, and two of the three virulence genes ( hlyA , iap or actA ) were simultaneously detected in six isolates.…”
Section: Discussionsupporting
confidence: 94%
“…Genes iap and hlyA are responsible for host cell invasion, while the actA gene is associated with cell-to-cell spread. Our finding agreed with those of previous studies conducted by Tahoun et al, and Şanlibaba et al [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], in which virulence genes were determined in L. monocytogenes isolated from raw milk, animals, and environmental samples. Our findings in virulence gene detection are also supported by the findings of [ 23 ], who reported that virulence genes hlyA , iap, and actA were the most recognized, with prevalence rates of 70.6%, 70.6%, and 52.9%, respectively, and two of the three virulence genes ( hlyA , iap or actA ) were simultaneously detected in six isolates.…”
Section: Discussionsupporting
confidence: 94%
“…The prevalence of L. ivanovii and L. welshimeri from milk of dairy cows were 6% and 4%, respectively in this study. In Turkey, nearly similar finding for L. ivanovii (5.4%) and L. welshimeri (4.5%) isolates from milk and milk products were detected by Sanlibaba et al [35]. On the other hand, lower prevalence of L. ivanovii (1.4%) and L. welshimeri (0.7%) in previous study were detected from cow milk samples by El-Sherbini et al [36] in Sharkia Governorate.…”
Section: Discussionsupporting
confidence: 73%
“…Aksoy et al [16] found L. monocytogenes in 16 (5.3%) dairy products in 300 food samples . Şanlıbaba et al [17] raported that Listeria spp. the prevalence were found in homemade cheese (9.09%), raw milk (8.19%) and white cheese (3.64%), respectively.…”
Section: Discussionmentioning
confidence: 99%